PENGARUH KEPEMIMPINAN DAN BUDAYA POLITIK TERHADAP PERILAKU PEMILIH TOWANI TOLOTANG DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Mustanir, Ahmad (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2016)
This research is aimed at observing the influence of leadership towards voter behavior among Towani Tolotang, particularly on the influence of political culture towards their voting behavior in Sub district of Maritengngae, District of Sidenreng Rappang. The population of this research is 1669 voters of Towani Tolotang. The samples are of 84 voters, selected by applying Slovin formula. The type of this research is quantitative descriptive based on surveys where questionnaires are the main instruments in collecting data. Among other ways of collecting data are observation, interviews, questionnaires, and library documents. The result of this research for X1 indicator shows that the level of leadership influence is 71% and is within the category of influencing. X2 indicator shows that the influence of political culture is 69% and within the category of influencing. Y indicator shows that voter behavior of Towani Tolotang is around 70.21% and within the category of influencing.